Association of Patterns of Otoferlin variant A1090E with Ethnicity, Developmental Milestones and Onset of Disease Course in Children with Non-Syndromic Hearing Loss - Riaz, Isma; Rashid, Amir; Arif, Amena; Mushtaq, Iffat; Baig, Zunaira Ali; Ahmed, Naeema (Pakistan Armed Forces Medical Journal, 2026)
Objective: To assess the association of variant genotypes with ethnicity, developmental milestones and onset of disease course in children with non-syndromic hereditary hearing loss.Study Design: Case-control study.Place and Duration of Study: ENT Department, Combined Military Hospital, Rawalpindi and CREAM Lab-I, Army Medical College, Rawalpindi, Pakistan from Jan to Dec 2022.Methodology: The study enrolled 200 subjects, aged 06 months to 10 years: 100 subjects with non-syndromic hearing loss (NSHL) were placed in Group-A, and 100 healthy individuals in Group-B. Blood samples were collected from each enrolled subject. DNA was extracted followed by polymerase chain reaction, and restriction fragment length polymorphism. Chi-square test was applied to check for association. Results: Analysis of the results indicated ethnicity regions as follows: Punjab 71% (NSHL) and 72% (controls); Khyber Pakhtunkhwa (KP) 19% (NSHL) and 15% (controls); Islamabad (Capital region) 06% (NSHL) and 05% (controls); Sindh 03% each (NSHL & controls) and Baluchistan 01% (NSHL) and 05% (controls). The wild genotype GG was the most common amongst subjects of all regions with highest frequency in Awan caste, both in case and control subjects. Statistically significant (p-value